Rapid Analysis of Cefazolin in Serum by High-Pressure Liquid Chromatography - Wold, John S. (1977)
A high-pressure liquid chromatography (HPLC) method has been developed for the analysis of cefazolin in serum. Serum was deproteinized by the addition of 6% trichloroacetic acid and injected onto a reverse-phase column with a mobile phase of 10 to 15% methanol in 1% aqueous acetic acid. Cefazolin chromatographed without interference from ultraviolet-absorbing components of serum, with a retention time of 3.1 min. Standard curves comparing peak area with concentration prepared from dog or human sera were linear over a range of 1.6 to 200 μg/ml. Results from the HPLC assay were compared with microbiological assays (cylinder plate method) on both standard serum samples and sera from dogs and human subjects receiving intramuscular cefazolin. The HPLC method was somewhat more accurate in comparison with the microbiological assay performed on serum samples of known concentration. The comparison of results from an analysis of serum levels of dogs or human subjects receiving cefazolin indicated that the two methods would lead to identical conclusions concerning pharmacokinetics or the achievement of therapeutic serum levels. The HPLC assay method presents an alternative to conventional microbiological assays, with marked improvement in speed (30 min) and considerable potential for future development.